DAMPAK KINERJA PENGELOLA BERDASARKAN KEPUASAN WISATAWAN - Iskandar, Iskandar (Komunitas Manajemen Kompetitif, 2024)
This study aims to determine the level of tourist satisfaction with natural tourist attractions and categorize which attractions need to be maintained, improved, and even reduced to gain efficiency. The research method used in this study is a descriptive method. The population in this study were visitors to the Henferd Land Riau natural tourist attraction. A total of 100 visitors were selected as samples using the accidental sampling technique. To determine the category position of each tourist attraction, the